2010
DOI: 10.1002/ejoc.200901362
|View full text |Cite
|
Sign up to set email alerts
|

β,meso‐Acetylenyl‐Bridged, Asymmetrical, Porphyrin Dyads – Synthesis, Spectral, Electrochemical and Computational Studies

Abstract: The first examples of β,meso-acetylenyl-bridged, asymmetrical, covalently linked, porphyrin dyads, containing two different subunits, such as ZnN 4 P-N 3 OP (1), ZnN 4 P-N 3 SP (2), ZnN 4 P-N 2 SOP (4) and ZnN 4 P-N 2 S 2 P (6), were synthesized by the coupling of a β-acetylenyl, ZnN 4 porphyrin with a mesobromoheteroporphyrin under mild, Pd 0 -catalyzed, coupling conditions. The dyads containing different types of metalfree subunits, such as N 4 P-N 3 SP (3), N 4 P-N 2 SOP (5) and N 4 P-N 2 S 2 P (7), were sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…For example, the porphyrin dyad 116 containing ZnN 4 porphyrin sub-unit and N 3 S porphyrin sub-unit, on excitation at 550 nm, the emission of ZnN 4 porphyrin quenched by 98% and the strong emission from N 3 S porphyrin sub-unit was observed due to energy transfer from ZnN 4 porphyrin subunit to N 3 S porphyrin sub-unit. 41 Similarly, all unsymmetrical porphyrin dyads 115-121 also showed an energy transfer from donor porphyrin unit to acceptor porphyrin unit as confirmed by steady state fluorescence studies.…”
Section: Ethyne Bridged Unsymmetrical Porphyrin Dyadsmentioning
confidence: 69%
See 1 more Smart Citation
“…For example, the porphyrin dyad 116 containing ZnN 4 porphyrin sub-unit and N 3 S porphyrin sub-unit, on excitation at 550 nm, the emission of ZnN 4 porphyrin quenched by 98% and the strong emission from N 3 S porphyrin sub-unit was observed due to energy transfer from ZnN 4 porphyrin subunit to N 3 S porphyrin sub-unit. 41 Similarly, all unsymmetrical porphyrin dyads 115-121 also showed an energy transfer from donor porphyrin unit to acceptor porphyrin unit as confirmed by steady state fluorescence studies.…”
Section: Ethyne Bridged Unsymmetrical Porphyrin Dyadsmentioning
confidence: 69%
“…41 The dyads Pd 2 (dba) 3 /AsPh 3 in toluene/triethylamine at 35°C for 4 h (Scheme XII). The metal free dyads 119-121 were synthesized by demetalation of dyads 116-118 respectively by treating the corresponding metalated dyad in CHCl 3 with TFA for 15 min (Scheme XII).…”
Section: Ethyne Bridged Unsymmetrical Porphyrin Dyadsmentioning
confidence: 99%
“…A series of ethyne-bridged unsymmetrical porphyrin dyads 76 – 77 containing two different porphyrin units were synthesized as shown in Scheme . The β- meso -ethyne-bridged unsymmetrical ZnN 4 –N 2 XY porphyrin dyads 76a – d were synthesized by coupling of β-ethynyl ZnN 4 porphyrin 75 with appropriate meso -bromo heteroporphyrin building block 13a/14a/34a/40a in the presence of Pd 2 (dba) 3 /AsPh 3 in toluene/triethylamine at 35 °C for 3 h. The ethyne-bridged unsymmetrical free base N 4 –N 2 XY porphyrin dyads 77a – c were synthesized by demetalation of appropriate ethyne-bridged ZnN 4 –N 2 XY porphyrin dyads 76a – d with trifluoroacetic acid (TFA) in CHCl 3 followed by simple column chromatographic purification. The fluorescence studies indicated a possibility of energy transfer at the singlet state from donor porphyrin unit to acceptor porphyrin unit in all ethyne-bridged unsymmetrical porphyrin dyads.…”
Section: Covalently and Noncovalently Linked Heteroporphyrin-based Mu...mentioning
confidence: 99%
“…A series of ethyne-bridged unsymmetrical porphyrin dyads 76 purification. The fluorescence studies indicated a possibility of energy transfer at the singlet state from donor porphyrin unit to acceptor porphyrin unit in all ethyne-bridged unsymmetrical porphyrin dyads.…”
Section: Covalently Linked Heteroporphyrin-based Arraysmentioning
confidence: 99%
“…The yield improved to 55% at 75 ℃ for 6 h, and up to 82% at 85 ℃ (Table 1, Entries 3,4). Further rising temperature will not continuously increase the yield but lead to the increase of by-products (Table 1, Entries 5,6). So 85 ℃ was the better choice of reaction temperature.…”
Section: Resultsmentioning
confidence: 98%